Analisis Keterhubungan Konsep Merek dengan Nama Domain: Kajian Kekayaan Intelektual di Indonesia - Sholahuddin Al-Fatih (Fakultas Hukum, Universitas Internasional Batam, 2021)
Globalization has had a very significant impact on the pattern of human interaction. Migration from the citizen into the netizen era, slowly but surely will happen soon. Changes in this pattern of interaction is actually followed by changes in terms and systems that apply, for example in concern with the cyber law. Legal problems that did not happen in the real world, could happen in the virtual world. One form of problems that arise includes related disputes to domain ownership, concept of domain name law and the relationship between the concept of the trademark with the domain name. Legal products made by the government have not been thoroughly in providing legal protection for such domain name cases. So the authors feel the need to convey some legal analysis related to the connection between the concepts of trademark law with the law of domain names in Indonesia.